Knowledge, Attitude, and Practice of Malaria Community Worker towards Prevention and Control of Malaria in Kokap, Kulon Progo: A Pilot Study - Noor Afif Mahmudah; Intan Esaputri; Halwan Fuad Bayuangga; Nova Yuli Prasetyo Budi; Alif Kurniawan; Ditha Marissya Daud; Jonathan Hasian Haposan (Faculty of Medicine, Public Health, and Nursing, 2020)
Background: Malaria Community Worker (CMW) has a crucial role in malaria prevention and control in the community. However, a number of studies showed that there is a lack of competence from MCW in carrying out its duties. Knowledge, attitudes and practice (KAP) can represent the behavior about health services. Objective: This study aimed to assess the knowledge, attitudes and practice of the Malaria Community Worker towards prevention and control of malaria in Kokap, Kulon Progo. Methods: KAP survey with cross-sectional design was conducted in this study. CMW from Puskesmas Kokap I (n = 8) was asked to fill out a KAP questionnaire. Descriptive statistics and inferential tests were used to analyze the data. Data were analyzed by IBM SPSS Statistics Version 25. Results: The study found that 100% of respondents (n = 8) obtained high knowledge scores with the highest aspect on understanding about malaria and the lowest on diagnosis. The attitude score showed a moderate attitude for 100% of respondents (n = 8) with the highest aspect was fogging for malaria prevention and the lowest was the attitude that malaria is a serious disease. Meanwhile, the score of practice described good practice in 100% of respondents (n = 8) with the lowest part was compiling daily/weekly reports to the malaria program coordinator of Primary Health Care. From the observations, there was no significant correlation (p> 0.05) between demographic characteristics and between knowledge, attitudes and practice. Conclusion: The CMWs had a high knowledge score, moderate attitude, and good practice towards malaria prevention and control. Further studies with a larger sample are recommended for future study. CMW training is also recommended to improve the KAP of CMW.